NUTRIENTS INTAKE AND NUTRITIONAL STATUS OF STREET CHILDREN IN BANDUNG - Rita Patriasih; Isma Widiaty; Mira Dewi; Dadang Sukandar (Jurnal Gizi dan Pangan, 2010)
The objectives of this research were to analyze food habits and nutrients intake, and health and nutritional status of street children. The research was carried out in the City of Bandung, West Java; Indonesia. A sample of 324 street children was selected randomly. The sample consisted of 232 boys and 92 girls. The data obtained from questionnaires. Means, standard deviation, frequency and proportion were calculated with a combination of software applications:  Microsoft Excel and Statistical Analysis System. The result showed the level of consumption adequacy did not meet the recommended dietary allowances i.e. with the shortage of 10-15%, this is an indication that the street children should be aware of their daily food consumption. The most common diseases suffered by the respondents were acute respiratory infections (ARI) (47%). In addition, 22.7 % and 18.4 % of them suffered from diarrhoea and skin diseases, respectively. Blood haemoglobin status of street children shows that the incidence of anemia was 29.3%. Based on the classification of nutritional status, 42.7% and 80.4 % of street children were underweight and stunted, respectively.